INTENAL SUPERVISION OF SCHOOL AFFECTING THE LEARNING MANAGEMENT OF TEACHERS UNDER SUPHANBURI PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Jaisa, Nutchanart; Srisopha, Yothin (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2026)
The purposes of this research were to 1) study the level of internal supervision; 2) study the level of the teaching management of teachers; 3) study the relationship between internal supervision and teaching management of teachers; and 4) formulate the predictive equation of internal supervision on the teaching management of teachers under the office of Suphanburi Primary Educational Service Area 3. The samples consisted of 310 teachers under the office of Suphanburi Primary Educational Service Area 3. The data collection instrument was a questionnaire. Statistical analysis was represented in frequency, percentage, mean, standard deviation, Pearson’s product moment correlation coefficient and stepwise multiple regression analysis. The results showed that: 1) Internal supervision was generally a high level. 2) The teaching management of teachers was generally a high level. 3) Internal supervision had a positive relationship with the teaching management of teachers at a high level with the statistical significant at .01 level. 4) Teamwork (X3) Human Resource Management (X6) Professional Development (X2) and Classroom Action Research (X5) together explained learning management of schools with the statistical significance at .01 level. These parameters explained the variance of the teaching management of teachers at the percentage of 72.60 The equation in raw score was as follows: = 1.27 + 0.40 (X3) + 0.10(X6) + 0.17(X2) + 0.08(X5) The equation in standard score was as follows: = 0.59(Z3) + 0.17(Z6) + 0.20(Z2) + 0.13(Z5)